Impact of in shoe and barefoot placed frontal wedges on plantar loading: A systematic review - Martínez-Rico, Magdalena; Deschamps, Kevin; Gijón-Noguerón, Gabriel; Ortega-Ávila, Ana Belén (Elsevier, 2022)
Eleven papers were included in the final review. Four were cross-over studies, other four were quasi-experimental studies and three were RCTs. These eleven studies included 320 patients, with ages ranging from 20 to 60 years. Regarding the risk of bias, most of the observational studies and RCTs had a moderate level of quality. Conclusions: The results suggest that lateral wedges are more effective, producing a lateral shift of the centre of pressure and increasing the pressure. Regarding the impact on the peak impact force there seems to be less consensus among the published data.
Keywords: Pies; Foot; Wedge; Foot orthoses; Custom-made orthoses; Systematic review